Comparative research on improving the thermal environment of traditional dwellings with attic space in Southern Shaanxi region, China - Xu, Juan; Xu, Beiyang; Yang, Wenting; Zhu, Caixia; Li, Qiang (Case studies in thermal engineering, 2024)
The ecological construction experience of traditional dwellings has been widely recognized. Hanzhong city belongs to the Hot Summer and Cold Winter zone, and the attic space is a common climate strategy in this area. The research takes a traditional dwelling in the region as an object in order to analyze the influence on the thermal environment of the attic. Firstly, we adopt field investigation and measurement to calculate the neutral temperature of 13.85 °C and 26.21 °C in winter and summer, respectively. It achieves the First-level comfortable zone, which ranges from 11.47 °C to 16.22 °C in winter and from 23.03 °C to 29.39 °C in summer. Then, comparative analysis reveals that the dwelling with attic space has a more comfortable and stable thermal environment than that without an attic through simulation. The indoor average operating temperature of dwelling with attics is 2.52 °C higher than that of a dwelling without attics in winter. On the contrary, the value decreases by 4.93 °C between those in summer. Finally, it shows that the attic space can increase the comfort duration by 995 h and 382 h, and reduce energy consumption by 1136.53kw and 566.43kw in winter and summer. Therefore, attic space adapts to the local climate and improves the indoor thermal environment significantly.